Application of Picture and Picture Model to Increase Description Writing Skills in Class III Students of MI Miftahul Mubtadiin Kedungwaru Kunduran Blora - Sangadah, Nur (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to improve students' writing skills using pictures and pictures at MI Miftahul Mubtadiin Kedungwaru Kunduran Blora. This research method used the PTK approach and analysis by carrying out Cycle 1 and Cycle 1. The subjects of this research were teachers and 22 class III students consisting of 10 male students and 12 female students. II Research Results 1) The teacher's skills in learning to write descriptions by applying the Picture and Picture model have increased. In cycle I, the score was 31 with good criteria, and in cycle II, the score increased to 36 with very good criteria. 2) Student activity in learning to write descriptions by applying the Picture and Picture model has increased. In cycle I, the score was 25.8 with good criteria, and in cycle II, the score increased to 29.5 with good criteria. 3) Student learning outcomes in the form of descriptive writing skills have increased. In the first cycle of the second meeting the average value was 72 with a completeness percentage of 72%, in the second cycle of the second meeting the average value reached 80 with a completeness percentage of 94%. Based on these data, it can be seen that there is an increase in student learning outcomes from the beginning of cycle I to the end of cycle II. This has achieved a predetermined success indicator of classical learning completeness, namely 75% with KKM > 65 it is proven that the application of the Picture and Picture model can improve teacher skills, student activity, and student learning outcomes in the form of students' writing skills.